Translational regulation of the human erythropoietin transcript by an upstream open reading frame - Barbosa, Cristina (2012)
Among the various cis-acting elements in mRNAs that participate in regulating protein synthesis are AUG codons within transcript leader sequences (uAUGs) and, in some cases, associated short upstream open reading frames (uORFs). Although about 15% of the human mRNAs present uORFs (mainly, those transcripts encoding growth factors or hormones), there is no general model for the mechanism by how and when an uORF downregulates the main ORF expression. Leaky scanning and reinitiation are mechanisms that allow translational control of the main ORF in a transcript bearing at least one uORF. In the leaky scanning mechanism ribosomes either ignore the uAUG codon and scan past it or recognize it, initiating translation. Short regulatory uORFs may also permit the small ribosomal subunit to stay mRNA-bound after termination and resume scanning for efficient reinitiation downstream at the main ORF. Even though, short uORFs may also downregulate expression of a main ORF by their special ability to mediate ribosome stalling at coding or termination codons, or by influencing the mRNA stability through the nonsense mediated mRNA decay (NMD) pathway. Erythropoietin (EPO) is a glycoprotein synthesized and released mainly from the kidney, with a key role in hematopoiesis. However, many other non-hematopoietic functions have recently been reported. Consequently, it might be used as a therapeutic target for the treatment of several human disorders. Understanding the molecular mechanisms of translational control of EPO mRNA may be valuable in the determination of these therapies. Knowing that human EPO transcript presents a 5’ leader with 181 nucleotides containing a 14-codon-uORF and given that it seems to be conserved among different species, which might indicate its role in translational regulation, we aimed to prove this hypothesis. To analyze the effect of this uORF, HepG2 and HEK293 cells were transfected with several constructs carrying the luciferase reporter gene with the intact or disrupted uORF. Luciferase activity was measured by luminometry and normalized to the corresponding mRNA levels to obtain translation efficiencies. The mRNA levels were quantified by RT-qPCR. Results show that the EPO uORF can decrease the main ORF translational efficiency in about 70%. In addition, our data support the conclusion that reinitiation, and in less extent leaky scanning, are responsible for the main ORF translation. Furthermore, this uORF does not block the translational machinery and does not trigger NMD. The interaction between the EPO uORF and its 3’ untranslated region (3’UTR) was also analyzed. Results show that the 3’UTR is able to increase the protein levels independently of the uORF.